Miniature Sensor Irradiation Tests Under Steady-State and Transient Conditions at MIT Research Reactor (MITR) and Transient Reactor Test Facility (TREAT). (2nd June 2020) - Sun, Kaichao; Carpenter, David; Ames, Michael; Dave, Akshay J.; Hu, Lin-Wen
Abstract: The Transient Reactor Test (TREAT) Facility at Idaho National Laboratory (INL) was officially restarted in 2017. In support of its restart project, investigations are taking place into the refurbishment and upgrade of TREAT's experiment systems with modern technology. In considering augmenting the current TREAT instrumentation, a variety of miniature neutron and gamma sensors that may be able to operate in-core will be irradiated under steady-state and transient conditions. The TREAT instrumentation is typically calibrated at steady state below 100 kW. This power level features a thermal flux similar to the Massachusetts Institute of Technology Research Reactor (MITR) at less than 100 kW. Low-power MITR operation was therefore chosen for initial instrumentation benchmarking. Following the MITR runs, the entire test assembly was shipped to INL. Shaped and temperature-limited transients were performed using TREAT's M8-Calibration vehicle. A total of three test rounds has taken place, including two 1-week sessions at MITR and one 2-week session at TREAT. Overall, successful performance for the majority of the tested detectors is concluded under steady-state and transient conditions. These miniature sensors are capable of recognizing accurate full-width at half-maximum of the reactor pulse. However, compared to operation channels located at the TREAT biological shield, all in-core instrumentations show certain degrees of underestimation of the peak power magnitude.